SAT0105 Summacta: A Randomized, Double-Blind, Parallel Group Study of the Safety and Efficacy Of Tocilizumab SC Versus Tocilizumab IV, in Combination with Traditional Dmards in Patients With Moderate to Severe Ra. (23rd January 2014) - Burmester, G. R.; Rubbert-Roth, A.; Cantagrel, A.; Hall, S.; Leszczynski, P.; Feldman, D.; Rangaraj, M. J.; Roane, G.; Ludivico, C.; Mysler, E.; Rowell, L.; Vranic, I.
Abstract : Background: The efficacy and safety profile of intravenous (IV) tocilizumab (TCZ) has been well established in patients (pts) with rheumatoid arthritis (RA). The aim of a subcutaneous (SC) TCZ dosing regimen is to provide the convenience of patient home use and self-administration. In the BREVACTA study, the primary endpoint was met by demonstrating superiority of TCZ SC 162 mg q2w over placebo for ACR20 response at 24 weeks (ACR 2012). Objectives: The objective of SUMMACTA study was to compare the efficacy and safety of TCZ SC and TCZ IV regimens in pts with adult RA who had an inadequate response to DMARDs (up to 20% may have failed one or more anti-TNF agents). Methods: SUMMACTA is a 2-year, Phase 3 trial, which is a randomized, active controlled, parallel group study that includes a 24-week double-blind (DB) period, followed by a 72-week open-label phase. During the DB period, pts received TCZ SC 162 mg qw + placebo IV q4w or TCZ IV 8mg/kg q4w + placebo SC qw, in combination with traditional DMARDs. The primary endpoint was the proportion of patients achieving an ACR20 response at Week 24. The hypothesis of non-inferiority of TCZ SC with respect to TCZ IV regarding ACR20 response was tested by means of the 95% confidence interval (CI) and with a 12% non-inferiority margin (NIM). Additional clinical efficacy, immunogenicity and safety assessments were evaluated as secondary outcomes. Pts were stratified at baseline by body weight and region. Results: A total of 1262 pts were enrolled globally. All patients' baseline characteristics were well balanced between TCZ SC and TCZ IV groups, including age, RA disease duration and DAS 28-ESR. At Week 24, 69.4% (95% CI: 65.5, 73.2) of TCZ SC-treated pts achieved an ACR20 response versus 73.4% (95% CI: 69.6, 77.1) of TCZ IV-treated pts. The weighted difference between groups was -4.0% [95% CI: -9.2, 1.2]) and a 12% NIM was met. ACR50/70 responses, disease activity and physical function improvements were also comparable between the TCZ SC and TCZ IV groups. Up to Week 24, the proportions of pts with at least one adverse event (AE) or serious AE were 76.2% and 4.6%, respectively, in the TCZ SC group compared with 77.0% and 5.2%, respectively, in the TCZ IV group. The most common AE in both groups was infection. Injection site reactions occurred more frequently in the TCZSC group than the TCZ IV group (10.1% vs 2.4%, respectively); but none required dose interruption or study withdrawal. No anaphylaxis was reported over the 24-week period. Conclusions: TCZ SC 162mg qw demonstrated efficacy and safety profile comparable to TCZ IV 8mg/kg q4w. The TCZ-SC formulation could provide an additional, more convenient administration option and opportunity for home injection for patients with RA. Disclosure of Interest: G. Burmester Grant/research support from: Roche, Abbott, Pfizer, UCB, BMS, MSD, Consultant for: Roche, Chugai, Pfizer, UBC, BMS, Speakers bureau: Roche, Pfizer, MSD, BMS, Abbott, A. Rubbert-Roth Grant/research support from: Roche, Pfizer, Consultant for: Roche, Chugai, Pfizer, MSD, Abbott, UCB, Speakers bureau: Roche, UCB, A. Cantagrel Grant/research support from: UCB, Pfizer, Consultant for: BMS, Chugai, Roche, UCB, Abbott, Pfizer, S. Hall: None Declared, P. Leszczynski Consultant for: Roche, D. Feldman: None Declared, M. Rangaraj Grant/research support from: Roche, G. Roane: None Declared, C. Ludivico Grant/research support from: Roche, BMS, Pfizer, Human Genome Science, Lilly, Sanofi-Aventis, Speakers bureau: BMS, E. Mysler Grant/research support from: Roche, Consultant for: Roche, Speakers bureau: Roche, L. Rowell Employee of: Roche, I. Vranic Employee of: Roche